N-(phenylsulfonyl)-glycine: a new contaminant in sewage- and surface water - Krause, Sonja; Niedan, Volker Wolfgang; Schöler, Heinz Friedrich (Chemosphere, 1998)
River samples (e.g. river Rhine, river Neckar; Germany) and samples from five communal sewage treatment plants were investigated for N-(phenylsulfonyl)-glycine, -alanine and -sarcosine, as well as for the corresponding p-toluene analogues. As result of this screening we identified N-(phenylsulfonyl)-glycine as a hitherto unknown polar contaminant. In surface waters the concentrations of N-(phenylsulfonyl)-glycine ranged between 50 and 850 ng/l. In communal sewage treatment plants the concentrations varied: The substance was only found in one influent with a concentration of 1200 ng/l; in the biological step and in the effluent its concentrations ranged from 80 to 300 ng/l. N-(phenylsulfonyl)-alanine, N-(p-toluenesulfonyl)-glycine, -sarcosine and -alanine were found neither in surface nor in sewage waters.
Gesehen am 17.11.2022